Avifauna urbana nas praças públicas em Iporá, estado de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Few bird’s studies have been developed at the Goiás State municipalities. This work has analysed the bird’s assemblages into eleven public squares from Iporá urban zone. The data were sampled monthly between July 2019 and June 2020, with the exception of March due to the COVID-19 pandemic, totalizing 11 sample turns (N=11), and point counts was the methodology used for data. A total of 63 species were recorded. The Jackniffe1’s estimated richness have demonstrated a satisfactorily number of species both to the total data and any public square alone. The occurrence category have shown most resident and probable resident species. The categories to anthropogenic impacts have demonstrated a greatest number of low sensitivity species, despite the chestnuteared Aracari Pteroglossus castanotis Gould, 1834 and red-and-green Macaw Ara chloropterus Gray, 1859 were classified as high sensitivity to anthropogenic impacts. Ochiai’s similarity analysis have demonstrated three distinct groups: the “K” square without trees in a group alone (similarity=0.62), a second group with more central squares (0.72), and a third group composed by squares with more trees and minus traffic (0.77). Insectivores, frugivores and omnivores were the most representative trophic categories both to the total and any square. Non-metric Multi-dimensional Scaling (NMDS) have shown the number of trees as the only environmental variable that affect positive and significant for the bird species richness. We recommend a greater planting of medium and large trees in the municipal squares and minus car transit, thus contributing to the maintenance and expansion of the bird fauna present in the same. The tree’s planting in these squares is important for both maintenance and widely your bird communities, and more studies in urban landscapes is important to understand urban bird’s in interior of the Goiás state
Bird community in public squares from Iporá, state of Goiás
Keywords: Brasil Central; Ambiente Urbano; Ornitologia; Variáveis Ambientais; Aves; Pássaros; Central Brazil; Urban Environment; Ornithology; Environmental Variables; CIENCIAS BIOLOGICAS